When Teams Agree While Disagreeing: Reflexion and Reflection in Shared Cognition - Healey, Mark P.; Vuori, Timo; Hodgkinson, Gerard P. (Academy of Management Review, 2015)
Drawing on dual-systems theory, we propose a new typology for analyzing shared cognition in workgroups and teams that differentiates reflective (i.e., C-system) mental models formed through reasoning and deliberation from reflexive (i.e., X-system) representations that are more automatic, intuitive, and affective in nature. Our analysis demonstrates how team members’ X-system representations pertaining to the team’s task and its members can compete with shared C-system mental models of the task and team in terms of their respective effects on team functioning. We highlight the consequences for intrateam coordination when team members have similar C-system mental models but dissimilar X-system representations (illusory concordance) and when team members have similar X-system representations but dissimilar C-system mental models (surface discordance). Finally, we consider the implications of our arguments for extending current team cognition theory predicated on reflective cognition and suggest new directions for research on group cognition in organizations more generally.